Nurse Caring Behavior on Patient Satisfaction in Hospitals - Gurusinga, Rahmad (Universitas Aisyah Pringsewu, 2020)
The caring behavior of the nursing staff is important in fulfilling patient satisfaction, the behavior is an indicator of service quality at the hospital. This study aims to determine the relationship of nurses caring behavior with patient satisfaction, to identify the description of nurses caring behavior, and to identify the description of hospital patient satisfaction. The sampling technique used in this study was purposive sampling with a total sample of 136 patients. The instruments used to measure the variables in this study were the patient satisfaction questionnaire (PSQ) and caring behavior inventory (CBI). The data obtained were analyzed by the Spearman correlation test. After analyzing the data, r = 0.615 (p less than 0.05) is obtained, proving that there is a significant relationship between nurses caring behavior with patient satisfaction values. In this study also produced a description of nurses caring behavior and patient satisfaction which was categorized into four, namely 54.4% good, 34.5% enough, 10.3% less, and 0.7% bad for nurses caring behavior. While the picture of patient satisfaction is categorized as very satisfied amounting to 13.2%, satisfied 65.5%, dissatisfied 20.6% and very dissatisfied 0.7%. Based on the results of the study obtained it can be concluded that the caring behavior of nurses is directly proportional to the sense of patient satisfaction.Perilaku Caring tenaga keperawatan merupakan hal yang penting dalam pemenuhan kepuasan pasien, perilaku tersebut menjadi salah satu indikator mutu pelayanan pada rumah sakit. Penelitian ini bertujuan untuk mengetahui hubungan perilaku caring perawat dengan kepuasan pasien, untuk mengidentifikasi gambaran perilaku caring tenaga perawat, dan untuk mengidentifikasi gambaran kepuasan pasien rumah sakit. Teknik pengambilan sampel yang digunakan pada penelitian ini adalah purposive sampling dengan jumlah sampel sebanyak 136 pasien. Instrumen yang digunakan untuk mengukur variabel-variabel pada penelitian ini yaitu Patient Satisfaction Questionnaire (PSQ) dan caring behaviour inventory (CBI). Data yang diperoleh dianalisis dengan uji korelasi Spearman. Setelah dilakukan analisis data maka diperoleh nilai r=0.615 (p kurang dari 0,05), membuktikan ada hubungan yang signifikan perilaku caring perawat dengan nilai kepuasan pasien. Dalam penelitian ini juga menghasilkan gambaran perilaku caring tenaga perawat dan kepuasan pasien yang dikatagorikan menjadi empat yaitu baik sejumlah 54,4%, cukup 34,5%, kurang 10,3%, dan buruk 0,7% untuk perilaku caring perawat. Sedangkan gambaran kepuasan pasien yaitu katagori sangat puas sejumlah 13,2%, puas 65,5%, tidak puas 20,6% dan sangat tidak puas 0,7 %. Berdasarkan hasil penelitian yang diperoleh dapat disimpulkan bahwa perilaku caring tenaga perawat berbanding lurus dengan rasa kepuasan pasien.